Communication as a life process. - Boguslawska-Tafelska, Marta; Haładewicz-Grzelak, Małgorzata (Studies in ecolinguistics, 2019)
This volume is a collection of texts authored by an international team of linguistic scholars who provide their response to the concept of 21st century holism in language studies. The expertise of its contributors is reflected in the thematic scope of the book; it discusses topics such as the concept of harmony in interpersonal communication, semiotic and cultural phenomena handled by discourse analysis, selected aspects of religious discourse, and the study of proverbs or educational processes, to name but a few. 21st century holism embraces a solid theoretical base in post-Newtonian physics.